Food neophobia among Brazilian children : prevalence and questionnaire score development - Almeida, Priscila Claudino de (2022)
This study aims to create and validate a score to classify food neophobia among Brazilian children (from the ages of 4 to 11 years) and investigate the prevalence of food neophobia. This descriptive cross-sectional population-based study is conducted following three steps: (i) the application of an instrument to identify food neophobia in Brazilian children by their caregivers; (ii) the instrument’s score definition; and (iii) the evaluation and characterization of the national prevalence of food neophobia among Brazilian children. The scores were categorized into three levels, based on the tertial approximation: low, moderate, and high. The study had 1112 participants, and the prevalence of high food neophobia was observed in 33.4% of Brazilian children. The prevalence of food neophobia allowed us to identify this behavior in Brazilian children and better understand the population. Boys were significantly more neophobic than girls. The general neophobia score and domains did not significantly differ between Brazilian regions and age groups. It is worrying that food neophobia did not decrease with advancing age. The score for the complete instrument with 25 items, or the 3 domains, makes its use practical. It can be used to assess neophobia with more caution, evaluate the most neophobic children, and enable more targeted professional interventions to promote healthier and sustainable eating habits.